1339 IMPROVING INPATIENT MANAGEMENT OF DELIRIUM IN A DISTRICT GENERAL HOSPITAL. (16th January 2023) - Juwarkar, A; Ahmed, S; Franks, S; Ring, A
Abstract: Background: Delirium is a common clinical condition associated with increased morbidity and mortality, and prolonged hospital stay. Early detection is vital to improving management of the condition and improving outcomes. Aims: Improve delirium detection using the 4AT screening tool as a validated approach; Improve delirium management across multiple domains using the PINCH ME approach; documented attempt at collateral history within 24 hours of recognition of delirium; obtain serological confusion screen in patients with recognised delirium. (100% each) Method: Plan Do Study Act (PDSA) method was used to conduct this Quality Improvement (QI) project over 12 months. Data was obtained from paper and electronic records in the medical wards with regards to 'at risk patients' (i.e. over 65y, acutely unwell, background of cognitive impairment and/or acute fracture). The use of 4AT or alternative delirium screens from the emergency department (ED) and medical teams were noted. Assessment for pain, urinalysis, serological screens, bowel and nutrition review including MUST scores, medication reviews were looked for. Interventions included presentation and education at the medicine grand round, publishing a poster, and a PINCHME alert sticker for the medical notes to use at time of assessment. 2 PDSA cycles were completed and post sticker results obtained. Results: Baseline data shows that collateral history was attempted for 70% patients - improved to 100% after sticker use. Use of validated screening test from 15% to 100% after sticker use. Nutrition assessment improved from 15% to 40%. Serological testing improved from 40% to 53%. 100% patients received a medication review after sticker use. Conclusion: Introduction of PINCHME sticker serves as a prompt to ensure holistic management. Currently delirium management is clinician dependent as there is lack of formal delirium management pathway. Further plan includes involving nursing staff and 'delirium champions' to bring about a formal pathway for lasting change.